Antioxidant and Adaptative Response Mediated by Nrf2 during Physical Exercise - Nancy Vargas-Mendoza; Ángel Morales-González; Eduardo Osiris Madrigal-Santillán; Eduardo Madrigal-Bujaidar; Isela Álvarez-González; Luis Fernando García-Melo; Liliana Anguiano-Robledo; Tomás Fregoso-Aguilar; José A. Morales-Gonzalez (MDPI AG, 2019)
Nuclear factor erythroid 2-related factor 2 (Nrf2) is a powerful nuclear transcription factor that coordinates an antioxidant cytoprotector system complex stimulated by the increase in inoxidative stress (OS). In the present manuscript, we conduct a review on the evidence that shows the effect different modalities of physical exercise exert on the antioxidant metabolic response directed by Nrf2. During physical exercise, the reactive oxygen species (ROS) are increased; therefore, if the endogenous and exogenous antioxidant defenses are unable to control the elevation of ROS, the resulting OS triggers the activation of the transcriptional factor Nrf2 to induce the antioxidant response. On a molecular basis related to physical exercise, hormesis maintenance (exercise preconditioning) and adaptative changes in training are supported by a growing body of evidence, which is important for detailing the health benefits that involve greater resistance to environmental aggressions, better tolerance to constant changes, and increasing the regenerative capacity of the cells in such a way that it may be used as a tool to support the prevention or treatment of diseases. This may have clinical implications for future investigations regarding physical exercise in terms of understanding adaptations in high-performance athletes but also as a therapeutic model in several diseases.